1985
DOI: 10.1093/oxfordjournals.aje.a114007
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Systolic Hypertension in 14 Communities1

Abstract: In the Hypertension Detection and Follow-up Program, 158,906 individuals from 14 communities around the United States had their blood pressure measured in their homes in 1972-1973. Of the total population screened, 2.4% had isolated systolic hypertension (systolic blood pressure greater than or equal to 160 mmHg and diastolic blood pressure less than 90 mmHg). Isolated systolic hypertension was present for 0.5% of those aged 30-39 years and 6.8% among those aged 60-69 years. The prevalence in blacks and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Pulse pressure (PP), defined as the difference between SBP and diastolic BP (DBP), is usually employed to explore this component. In many studies, [3][4][5][6][7][8][9] subjects with higher PP were found to have a higher risk than subjects with lower PP values at the same age. Some of these studies, nevertheless, took into consideration hypertensive patients 10,11 or groups of subjects 12 rather than people from the general population, and the role of gender was often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse pressure (PP), defined as the difference between SBP and diastolic BP (DBP), is usually employed to explore this component. In many studies, [3][4][5][6][7][8][9] subjects with higher PP were found to have a higher risk than subjects with lower PP values at the same age. Some of these studies, nevertheless, took into consideration hypertensive patients 10,11 or groups of subjects 12 rather than people from the general population, and the role of gender was often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…22 The other studies that have determined the prevalence of ISH among middleaged men and women in the population have usually reported lower estimates than ours. [8][9][10][11]23,24 Since different methods have been used, the comparisons of prevalence estimates must, however, be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In most epidemiological studies, where multiple recordings are usually not possible, ISH has been defined as SBP у160 mm Hg in the presence of DBP of either less than 90 or 95 mm Hg. ISH has been associated with increased cardiovascular mortality and morbidity not only in the elderly 4,5 but also in middle-aged persons, [6][7][8][9][10][11] and a SBP level of 140-159 mm Hg already seems to increase the risk of CVD. 12,13 The prevalence of ISH increases in both sexes with age.…”
Section: Introductionmentioning
confidence: 99%
“…In the US Hypertension Detection and Follow-up Programme the mortality rate among those with ISH was 17.6%, and 7.5% in subjects with a BP within normal limits. 39 Multiple regression analysis showed that 1 mm Hg increase in SBP was associated with a 1% increase in mortality. Similar results were observed in the Multiple Risk Factor Intervention Trial (MRFIT).…”
Section: Cardiovascular Riskmentioning
confidence: 98%